(untitled) (Fiep Bulletin - online, 2014)
The main goal of this research is determining the motor skills of students aged 10 and their impact on the interpersonal relationships in the classroom, the influence of motor abilities of students in their position-acceptance in a group or a class – on sociometric status of the group at students. The sample of respondents consists of 200 students (100 male&100 female) at the age of ten, who attend primary schools in the city of Skopje, Republic of Macedonia. The sample of variables consists of two anthropometric and six motor variables as well as 12 variables to determine the sociometric status of the group at students. Data obtained by using descriptive statistical procedures such as: arithmetic mean, standard deviation, skewness, kurtosis, minimum and maximum result will present the image of the researched statistical positions and also it will be helpful in the further interpretation of the survey results. Through the multiple statistical procedures the motor skills impact on the acceptance of the sociometric status of the group at students can be accurately located- regression analysis, where by partial regression coefficients and coefficients of multiple regression with the coefficient of determination will determine the impact of criteria variable on the system of predictors. By the results thus obtained a scientific conclusion is allowed on an appropriate level of statistical significance of .05, which notes that students who do sports and have good motor skills are positively accepted by their classmates. Students who do not do sports and have below average motor skills are usually those with the worst behavior in the class.